2019
DOI: 10.1111/iej.13109
|View full text |Cite
|
Sign up to set email alerts
|

Apical root canal anatomy in the mesiobuccal root of maxillary first molars: influence of root apical shape and prevalence of apical foramina – a micro‐CT study

Abstract: Aim To determine whether a relationship exists between the apical shape of roots and root canal system complexity by performing a micro‐computed tomography analysis. Methodology One hundred extracted permanent maxillary first molars were scanned using a micro‐computed tomography device at 19.6 μm voxel size. Two groups of mesiobuccal roots were formed according to the root aspect ratio value in the apical 3‐mm cross‐sectional level (‘<2 and ≥ 2.00’). Data were recorded regarding the number and presence of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…With the different types of micro-CT machines available in the market, it is not possible to recommend definite parameters for scanning; a pilot examination is usually needed for optimisation of the scanning parameters in terms of the amount of noise, contrast between dental tissues and clarity of structures, with considerations to the time per scan, storage and cost (Chavez et al, 2021). Indeed, information provided in related literature is also helpful-as an example, the voxel size for a human tooth ranges from <10 µm to about 30 µm (Ordinola-Zapata et al, 2019;Versiani et al, 2012Versiani et al, , 2016aZhang et al, 2014), which can be optimised based on the tooth type, study objectives and details needed for qualitative and quantitative analysis. The scanning itself is done automatically with no user interaction, but frequent supervision is advisable as several errors may occur such as X-ray source instability (du Plessis et al, 2017).…”
Section: B) Micro-computed Tomography (Micro-ct)mentioning
confidence: 99%
See 3 more Smart Citations
“…With the different types of micro-CT machines available in the market, it is not possible to recommend definite parameters for scanning; a pilot examination is usually needed for optimisation of the scanning parameters in terms of the amount of noise, contrast between dental tissues and clarity of structures, with considerations to the time per scan, storage and cost (Chavez et al, 2021). Indeed, information provided in related literature is also helpful-as an example, the voxel size for a human tooth ranges from <10 µm to about 30 µm (Ordinola-Zapata et al, 2019;Versiani et al, 2012Versiani et al, , 2016aZhang et al, 2014), which can be optimised based on the tooth type, study objectives and details needed for qualitative and quantitative analysis. The scanning itself is done automatically with no user interaction, but frequent supervision is advisable as several errors may occur such as X-ray source instability (du Plessis et al, 2017).…”
Section: B) Micro-computed Tomography (Micro-ct)mentioning
confidence: 99%
“…Micro‐CT technology provides opportunities for a wide range of measurements. The shape of a given object has indices for 2D measurements such as perimeter (P), area (A), form factor (FF), roundness (R), aspect ratio (AR), ellipticity/eccentricity (E), curvature (C), tortuosity (T) in addition to parameters related to 3D measurements such as volume (V), surface area (SA) and structure model index (SMI) (Filpo‐Perez et al, 2015; Ordinola‐Zapata et al, 2019; Versiani & Keleş, 2020; Versiani et al, 2011; Wirth, 2004). The algorithms and measurements used in micro‐CT software allow detailed quantitative descriptions of root and canal anatomy (Table 1, Figures 20–22), besides the high‐resolution qualitative presentations of the main and fine details.…”
Section: Analysis Of Laboratory and Clinical Root And Canal Anatomy S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, great progress has been made in the mechanical preparation of root canals; however, these methods are still unable to completely eradicate the bacteria within the root canal [ 3 , 4 ]. Irrigation is complementary to instrumentation in facilitating the removal of bacteria, debris, and the smear layer [ 5 ]. Previous studies have shown that instrumentation and irrigation with NaOCl eliminates bacteria in 50–75% of infected root canals at the end of the first treatment session, whereas the remaining root canals contain recoverable bacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%